Extraction and analysis of fixed oils from the seeds of Calophyllum inophyllum Linne (Fam. Guttiferae) (Bitaog) - Tabor, Juvy A.; Cruz, Ileana R.; Concepcion. Adoracion B. (Manila College of Pharmacy, University of the Philippines, 1990)
The seeds of Calophyllum inophyllum Linne (Fam. Guttiferae), commonly known as ?bitaog? or ?palomaria?, was found to yield 64.24% (v/w) oil and contains plant acids and tannins.
Determination of the physical properties of the oil extracted from the seed gave the following values: B.P = 252℃; n = 1.48; d15 = 0.9436.
The viscosity of the oil was determined to be 32 centipoises.
Chemical analysis of the oil resulted to: saponification value = 193.84; acid value = 24.62; iodine value = 107.36; and ester value = 161.12.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, 1990.
Keywords: Calophyllum inophyllum; Bitaog; Palomaria